Can current land and water governance systems promote sustainable and equitable large-scale agricultural investments in sub-Saharan Africa? - Williams, Timothy O.; Sidibe, Yoro (2015)
Ever since the oil, financial and food crises of 2008, sub-Saharan Africa has witnessed a marked increase in large-scale investment in agricultural land. The drivers of this investment are varied and include growing food, water and energy insecurity as well as social and economic interests of investors and recipient countries. The shape of these investments and their eventual outcomes are equally influenced by the existing land and water governance systems in the host countries. Based on fieldlevel research conducted in Ghana and Mali which covered six large-scale agricultural investments, this paper analyzes the current land and water governance systems in these two countries through the lens of land and water acquisition and initial outcomes. It highlights missed opportunities for sustainable and equitable large-scale agricultural land investments due to uncoordinated governance systems and failure to rigorously apply detailed rules and regulations that are already in place. It offers suggestions for revamping land and water governance to promote large-scale investments that will lead to equitable distribution of benefits and sustainable management of natural resources.